One religion too many : the religiously comparative reflections of a comparatively religious Hindu - Sharma, Arvind (State University of New York Press, 2011)
One Religion Too Many is a Hindu pilgrim's progress through the world's religious traditions. An eminent scholar of comparative religion, Arvind Sharma provides a firsthand account of how he came to be a party to the dialogue of religions--first with his own religion, then with the comparative study of religion, and finally with the religious universalism he has come to espouse because of this heritage. Starting with an account of the Hinduism of his family in Varanasi, India, Sharma then heads west, finding himself initially dumbfounded by the Christian Eucharist, wondering if there is a "Hinjew connection," grappling with Zen in Massachusetts, and pressed into service to teach about Islam. Sharma writes with a light touch, but even when his encounters and perceptions are amusing, they are always insightful and thought provoking. Western readers, in particular, will enjoy seeing their own traditions through the eyes of an Easterner who has come to know them well. Sharma's